Understanding Social Intelligence, Emotional Intelligence and Interpersonal Communication of Economic Education Students in the Learning Process - Warneri Warneri; Maria Ulfah; Okianna; M. Basri; Husni Syahrudin (Yayasan Ahmar Cendekia Indonesia, 2023)
Improving the quality of learning can occur if students' understanding of social intelligence, emotional intelligence and interpersonal communication is well understood in the learning process. Intelligent students will be able to identify various problems experienced during the learning process. One of the efforts to identify these problems is an understanding of the importance of social intelligence, emotional intelligence and interpersonal communication. The purpose of this counseling activity is to disseminate knowledge and understanding of students of economic education study program FKIP Untan Pontianak about social intelligence, emotional intelligence and interpersonal communication. The method used in this activity is counseling accompanied by discussion and question and answer. The activity was carried out face-to-face which was enthusiastically followed by students. The result of this activity is that the students of the Fkip Untan economic education study program have understood social intelligence, emotional intelligence and interpersonal communication well in the learning process